Effects of ballista and kilroy springs on palatally impacted canines: A finite element model analysis - Başer, Ecem Nagihan; Kaptan Akar, Nevin; Sayar, Gülşilay (Galenos Publishing House, 2023)
Objective: This study evaluated the stress distribution and displacement on impacted maxillary canines and their adjacent teeth of orthodontic forced eruption using Ballista and Kilroy springs by finite element model (FEM) analysis. Methods: Two different FEMs applying the same force level on an impacted canine tooth (Model 1: Ballista spring, Model 2: Kilroy spring) were conducted using FEM analysis and the principal stresses, von Mises stresses, and displacements were evaluated. Results: Von Mises values at the cusp tip of impacted canines were measured as 0.009896 N/mm2 in the Ballista model and 0.015334 N/mm2 in the Kilroy model. The highest value was measured in the buccal apex of the first premolar in both spring designs. The extrusion was observed in Ballista, and intrusion was observed in the Kilroy model at the apex of the first premolar. The Ballista model showed the highest value (0.003642 N/mm2) at the buccal tip of the first premolar, while in the Kilroy model, the highest measurement (0.002989 N/mm2) was shown at the incisal edge of the lateral tooth. Conclusion: Von Mises stress values were higher in the Kilroy model at the cusp tip and apical part of the impacted tooth than that in the Ballista model. The highest von Mises stress values were concentrated on the buccal root apex of the first premolar in both models. Although the amount of force applied by the springs was the same, the stress values were different depending on the spring design.
Keywords: Canine Impaction; Finite Element Analysis; Force; Ballista; Kilroy; Impacted Teeth